1996
DOI: 10.1007/bf02600159
|View full text |Cite
|
Sign up to set email alerts
|

Physician attitudes regarding telephone medicine

Abstract: Several physician attitudes regarding telephone medicine can be measured reliably. Our findings suggest that improving systems for managing patient calls and improving telephone training for physicians will improve physician satisfaction and confidence with the practice of telephone medicine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

1998
1998
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 19 publications
0
12
0
Order By: Relevance
“…The absence of a formal training curriculum in telephone management is not unique to this residency training program, 16 and the TELI group and other investigators have shown that the effective introduction of a telephone management training program is feasible and desirable. [17][18][19][20][21][22][23] The focus of this study was telephone calls made by patients to the covering practice physician, not to the patients' primary physician. Physician recommendations, patient relief, satisfaction, and outcomes may be different if the physician has a long-term relationship with the patient to whom they are giving medical advice over the telephone.…”
Section: Discussionmentioning
confidence: 99%
“…The absence of a formal training curriculum in telephone management is not unique to this residency training program, 16 and the TELI group and other investigators have shown that the effective introduction of a telephone management training program is feasible and desirable. [17][18][19][20][21][22][23] The focus of this study was telephone calls made by patients to the covering practice physician, not to the patients' primary physician. Physician recommendations, patient relief, satisfaction, and outcomes may be different if the physician has a long-term relationship with the patient to whom they are giving medical advice over the telephone.…”
Section: Discussionmentioning
confidence: 99%
“…Primary care physicians are often dissatisfied with telephone encounters and feel that many are inappropriate. 8,9 In studies of pediatricians, 42% of those based in HMOs and 45% of those in fee‐for‐service practices felt dissatisfied with their telephone systems. 10 Practicing internists have expressed a lack of confidence in their ability to practice telephone medicine.…”
Section: Problems With Telephone Practicementioning
confidence: 99%
“…10 Practicing internists have expressed a lack of confidence in their ability to practice telephone medicine. 8 They feel particularly uneasy about prescribing medications for telephone contacts, perhaps because they feel unprepared by their residencies for these interactions. 8 …”
Section: Problems With Telephone Practicementioning
confidence: 99%
“…The accuracy of the Content should not be relied upon and should be independently verified with primary sources of information. 10 Program directors were most interested in affecting residents' prescribing practices and improving telephone systems (e.g., defining responsibilities for handling calls, thorough documentation of calls, and ready chart availability). This article may be used for research, teaching, and private study purposes.…”
Section: Please Scroll Down For Articlementioning
confidence: 99%